Effectiveness and safety evaluation in the dyslipidemia treatment with statins - André Santos Silva; Túlio Ricardo Couto de Lima Souza; Allan Alves Freitas; Luciane Soares Lima; Almir Gonçalves WAnderley (São Paulo State University (UNESP), 2016)
Statins are used to reduce morbidity and mortality in patients with a high risk of cardiovascular disease. However, the use of statins does not ensure effectiveness and pharmacotherapeutic safety. In this context, the present study aimed to evaluate the effectiveness and safety of the therapy with statins in patients with dyslipidemia and high cardiovascular risk. To evaluate these parameters, this study selected 113 dyslipidemic patients with regular statins use of at least seven months. It was an observational cross-sectional study, based on data analysis collected from biochemical tests of patients with dyslipidemia in the public health system in the state of Pernambuco, Brazil. Isolated hypercholesterolemia was the most prevalent dyslipidemia type and the most used statin was atorvastatin (84%), followed by simvastatin (16%). The study observed no effectiveness in 58.4% of the patients; 28% had no safety in the treatment, and 48.3% were using doses above the standard dosage. Comparing effectiveness and safety between the same drugs, at standard dosage with higher dosages, there was not any statistical difference in biochemical test results. Therapeutic goals for LDL-C ≤ 70 mg/dL were found in 28% of cases. However, the useof doses above the standard dosage intended to reach very low LDL-C levels should be reevaluated, since there was no statistical difference in reducing the lipid profile, suggesting that the same results can be obtained with a lower standardized dose. This study provides  data relevant to the discussion of statins use and to the necessity of strengthening pharmacotherapeutic monitoring in dyslipidemia treatment. Keywords: Dyslipidemias. Drug Monitoring. Evaluation of Results of Therapeutic Interventions. Hydroxymethylglutaryl-CoA Reductase Inhibitors.